Method for testing shear expansion property and shear zone evolution of sandy soil
Through the combination of a CT machine and a triaxial instrument, the longitudinal section of the sand and soil sample in the three-axial shear process is scanned in real time, solving the problem of difficulty in testing the shear swelling of the sand and soil belt evolution in the prior art, and realizing detailed analysis and data collection of the structural evolution characteristics of the sand and soil sample.
Patent Information
- Application Number
- CN202411671153.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively test the shear swelling properties of sand and soil and the evolution of shear zones, especially during real-time dynamic scanning and triaxial testing.
A CT machine and a triaxial instrument were used to conduct a triaxial shear test on the sand and soil samples, and the longitudinal sections of the samples were scanned dynamically in real time to analyze the volume changes and the generation and development of shear belts.
Real-time observation and analysis of the meticulous structural evolution characteristics of sandy soil samples during the triaxial shearing process is achieved, providing detailed data on shear swelling and shear zone evolution, helping to understand the strength formation mechanism and damage process of particulate soil.
Smart Images

Figure CN119643321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of geotechnical and civil engineering technology, and in particular to a method for testing the shear dilatancy of sand and the evolution of shear bands. The research method is based on CT technology. Background Art
[0002] Granular materials are widely used in geotechnical and civil engineering fields, but granular materials will break under certain loads. When the particles are broken, their overall strength and compression characteristics will change, causing the overall structure to become unstable and resulting in catastrophic damage. Due to the development of internal pores and irregular external shape of granular soil, it is very different from terrestrial sediments, especially in terms of high compression, low strength and easy breakage. Granular soil will expand during the shear process. As a basic property of soil, shear dilatancy has always been an important aspect that scholars have been continuously studying. Moreover, the development of shear bands has always been a concern in the geotechnical engineering community. The study of shear bands plays a great role in people's further understanding of the strength characteristics, failure process and mechanical properties of the specimens. At present, the means to study dilatancy and the development of shear bands are very limited.
[0003] As an advanced non-destructive testing technology for materials, CT can scan the cross section of the sample, reconstruct its internal structure in two dimensions and three dimensions, and quantitatively measure the physical parameters inside the sample. At present, CT technology has been widely used in the study of the evolution of the microstructure of geotechnical engineering, and has achieved many excellent results. However, early studies all scanned the sample after unloading, which not only failed to capture the real-time changes of the sample, but also affected the sample during the cyclic loading process. With the improvement of instruments and equipment and the development of CT technology, more scholars have begun to scan the loading process of the sample in real time. However, due to the limitations of the instrument, many studies have focused on the cross-sectional scanning and analysis of the sample, and have not carried out the scanning of the longitudinal interface of the triaxial sample, nor have they observed the shear band development process and the law of shear dilatancy changes throughout the process.
[0004] Therefore, it is necessary for researchers in this field to provide a method to test the dilatancy of sand and the evolution of shear bands. Summary of the invention
[0005] The present invention provides a method for testing the shear dilatancy of sand and the evolution of shear bands. A CT machine is used in conjunction with a triaxial instrument to perform a microscopic real-time dynamic scan of a sand sample during a triaxial drainage shear process, observe the microscopic structural evolution characteristics, obtain a CT scan image of the longitudinal section of the sample, and analyze the volume change of the sand sample during the triaxial shear process and the generation and development process of the shear band.
[0006] The technical solution provided by the present invention is as follows:
[0007] A method for testing the dilatancy of sand and the evolution of shear bands comprises the following steps:
[0008] Step 1, preparing samples: collecting first soil samples and second soil samples from different target sites, washing and drying them respectively, performing screening tests on the first soil samples and the second soil samples to obtain particle grading curves of the first soil samples and the second soil samples, and then pressing the first soil samples, the second soil samples, and a mixture of the first soil samples and the second soil samples after drying respectively through a sample preparation instrument to obtain multiple samples;
[0009] Wherein, the first soil sample is coral sand, and the second soil sample is quartz sand.
[0010] Step 2: Vacuum and saturate the sample: put all the pressed samples together with the sample preparation mold of the sample preparation instrument into a vacuum saturation cylinder filled with water, place a permeable stone on the upper and lower parts of the sample preparation mold, vacuumize continuously, then put the sample preparation mold into a freezer for freezing, demould and sample loading, and dissolve naturally;
[0011] Step 3: using a CT-triaxial instrument to perform a triaxial shear test on the sample after natural dissolution, performing a microscopic real-time dynamic scan of the triaxial shear and compression process of the sample, and collecting test data;
[0012] The CT-triaxial instrument includes a pressure chamber, a volume pressure controller and a data acquisition box. During the test, the pressure chamber is placed vertically in the scanning hole of the CT machine. The volume pressure controller controls the pressure by the amount of pure water pumped in. The data acquisition box is used to collect the test data.
[0013] Step 4: After the test is completed, the sample after the test is taken out and sieved, and the particle crushing law of the sample is obtained according to the particle grading curve of the sample before and after the test; by performing deformation and strength characteristic analysis and structural evolution analysis on the test data, the purpose of testing the shear dilatancy and shear band evolution of the sample is achieved.
[0014] Furthermore, in step 1, the sample preparation instrument adopts a ring shear sample preparation device, and the ring shear sample preparation device includes a sample pressing device and a sample preparation mold;
[0015] The sieving test was carried out using special sieves with sieve hole diameters of 2 mm, 1.43 mm, 1.0 mm, 0.85 mm, 0.5 mm, 0.3 mm, 0.2 mm, 0.1 mm, 0.075 mm, 0.0385 and 0.01 mm, respectively.
[0016] Furthermore, in step 1, the first soil sample is coral sand, with a maximum porosity ratio of 1.41, a minimum porosity of 0.77, and a relative density of soil particles of 2.739;
[0017] The second soil sample is quartz sand, the maximum and minimum porosity ratios of the quartz sand are 0.725 and 0.485 respectively, and the relative density of soil particles is 2.691;
[0018] Among the samples pressed from the first soil sample, the second soil sample, and the mixture of the first soil sample and the second soil sample, all the samples have a relative density Dr=0.5, a confining pressure of 50 kPa, a shear rate of 0.1 mm / min, and a moisture content of 20%;
[0019] The sand mixing ratios of the mixture of the first soil sample and the second soil sample are 20%, 40%, 60% and 80% respectively.
[0020] Furthermore, in step 2, the sample is continuously vacuumed for 4 hours, the sample preparation mold is placed in a freezer for 2 hours, and the natural dissolution time is 8 hours.
[0021] Furthermore, in step three, the triaxial shear test is performed on the sample after natural dissolution using a CT-triaxial apparatus, comprising the following steps:
[0022] Connect the water inlet valve of the pressure chamber to the water pump, turn on the water pump to inject distilled water into the cavity of the pressure chamber, open the exhaust port on the upper part of the pressure chamber to ensure that all the air in the cavity of the pressure chamber is exhausted to avoid bubbles affecting the test results;
[0023] Adjusting the volume pressure controller so that the sample base rises slowly until the sample top cap contacts the upper wall of the pressure chamber;
[0024] The parameters of the confining pressure and the shear rate are input into the control interface of the CT-triaxial instrument to start the test. The data acquisition box starts to collect the test data of the sample. The test data includes principal stress difference, axial strain, and volume deformation data. The test data is presented in the form of graphics.
[0025] Furthermore, in step 1, the mass calculation process of each particle group in the mixture of the first soil sample and the second soil sample is as follows:
[0026] 1) According to the relative density Dr required for the test, the porosity ratio e of the first soil sample and the second soil sample is calculated using the following formula:
[0027]
[0028] In the formula, e max is the porosity ratio in the loosest state, called the maximum porosity ratio; e min is the minimum porosity, i.e. the porosity in the most dense state; e is the natural porosity;
[0029] 2) According to the void ratio, the dry density of the first soil sample and the second soil sample under the condition of known relative density can be obtained, and the calculation formula is:
[0030]
[0031] Where Gs is the relative density of particles, ρ w is the density of water, ρ w =1g / cm 3 ;
[0032] 3) During the calculation process, ensure that the volume V of the first soil sample c The second soil sample volume V q The sum of the volumes of the shear box remains unchanged;
[0033] 4) The mass m of the first soil sample can be calculated according to the set sand mixing rate Rs c and the mass of the second soil sample m q , the calculation formula of the sand mixing rate of the mixture is:
[0034]
[0035] Where, Rs is the sand mixing rate (%); m q is the mass of quartz sand in dry state (g), m c is the mass of coral sand in dry state (g); ρ dq is the dry density of quartz sand (g / cm3), ρ dc is the dry density of coral sand (g / cm3); V is the sample volume (cm3), which is equal to the shear box volume, V c is the volume of coral sand (cm3); when the sand mixing rate is 0%, V = V c , it is a pure coral sand sample; when the sand mixing rate is 100%, it is a pure quartz sand sample.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention provides a method for testing the dilatancy of sand and the evolution of shear bands. The method uses a CT machine in conjunction with a triaxial instrument to perform a microscopic real-time dynamic scan of a granular soil sample during a triaxial drainage shear process, observe the microscopic structural evolution characteristics, obtain a CT scan image of the sample longitudinal section, and analyze the volume change of the granular soil sample during the triaxial shear process and the generation and development process of the shear band. The crushing mechanism of granular soil and its mixture is analyzed by combining the change of CT value with the screening test. The research results are expected to provide microscopic structural test data and theoretical analysis basis for further understanding the strength formation mechanism of granular soil, the law of shear band formation and the particle crushing characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The flowchart of the method for testing the dilatancy of sand and the evolution of shear band of the present invention is as follows;
[0039] Figure 2 It is a particle gradation curve diagram before and after the test in the embodiment of the present invention;
[0040] Figure 3 A schematic diagram of a sample after loading in an embodiment of the present invention;
[0041] Figure 4 The deviator stress-axial strain curve diagram of coral sand and mixed material in the embodiment of the present invention;
[0042] Figure 5 is a volume strain-axial strain relationship curve diagram of different sand mixing rates (Rs=0%, Rs=20%, Rs=40%, Rs=60%, Rs=80% and Rs=100%) during shearing under a confining pressure of 50 kPa in an embodiment of the present invention;
[0043] Figure 6 This is a graph showing the maximum longitudinal section of sample 1 changing with axial strain in an embodiment of the present invention;
[0044] Figure 7 This is a graph showing the maximum longitudinal section of sample 2 changing with axial strain in an embodiment of the present invention;
[0045] Figure 8 This is a graph showing the maximum longitudinal section of sample 3 changing with axial strain in an embodiment of the present invention;
[0046] Fig. 9 This is a graph showing the maximum longitudinal section of sample 4 changing with axial strain in an embodiment of the present invention;
[0047] Fig.10 This is a graph showing the maximum longitudinal section of sample 5 changing with axial strain in an embodiment of the present invention;
[0048] Fig.11 This is a graph showing the maximum longitudinal section of sample 6 changing with axial strain in an embodiment of the present invention;
[0049] Fig.12 The shear band and the actual picture after shearing are completed in the embodiment of the present invention;
[0050] Fig.13 This is a schematic diagram of the CT value measurement area in an embodiment of the present invention;
[0051] Fig.14 It is a graph of ME value-axial strain curve in an embodiment of the present invention;
[0052] Fig.15 It is the SD value-axial strain curve diagram in the embodiment of the present invention. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the embodiments described below are part of the embodiments of the present application, rather than all of the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0054] See also Figure 1 The present invention provides a method for testing the shear dilatancy of sand and the evolution of shear bands, comprising the following steps:
[0055] Step 1, prepare samples: collect the first soil sample and the second soil sample from different target sites, wash and dry them respectively, perform screening tests on the first soil sample and the second soil sample, obtain the particle grading curves of the first soil sample and the second soil sample, and then use a sample preparation instrument to press the first soil sample, the second soil sample and the mixture of the first soil sample and the second soil sample after drying to obtain multiple samples. Among them, at least one of the first soil sample or the second soil sample is granular soil, and the granular soil is selected from coral sand.
[0056] Step 2, vacuum saturation treatment of the sample: put all the pressed samples together with the sample preparation mold of the sample preparation instrument into a vacuum saturation cylinder filled with water, place a permeable stone on the upper and lower parts of the sample preparation mold, continuously vacuum, and then put the sample preparation mold into the freezer for freezing, demolding and sample loading, and naturally dissolve.
[0057] Step 3: Use a CT-triaxial instrument to perform a triaxial shear test on the sample after natural dissolution, perform a microscopic real-time dynamic scan of the triaxial shear and compression process of the sample, and collect test data.
[0058] Among them, the CT-triaxial instrument includes a pressure chamber, a volume pressure controller and a data acquisition box. During the test, the pressure chamber is placed vertically in the scanning hole of the CT machine. The volume pressure controller controls the pressure by the amount of pure water pumped in, and the data acquisition box is used to collect the test data.
[0059] Step 4: After the test is completed, the sample after the test is taken out and sieved, and the particle crushing law of the sample is obtained according to the particle grading curve of the sample before and after the test; by performing deformation and strength characteristic analysis and structural evolution analysis on the test data, the purpose of testing the shear dilatancy and shear band evolution of the sample is achieved.
[0060] Optionally, in step 1, the sample preparation instrument adopts a ring shear sample preparation device, and the ring shear sample preparation device includes a sample pressing device and a sample preparation mold;
[0061] The sieving test was carried out using special sieves with sieve hole diameters of 2 mm, 1.43 mm, 1.0 mm, 0.85 mm, 0.5 mm, 0.3 mm, 0.2 mm, 0.1 mm, 0.075 mm, 0.0385 and 0.01 mm, respectively.
[0062] Optionally, in step 1, the maximum porosity ratio of the coral sand is 1.41, the minimum porosity ratio is 0.77, and the relative density of soil particles is 2.739;
[0063] The second soil sample is quartz sand, the maximum and minimum porosity ratios of the quartz sand are 0.725 and 0.485 respectively, and the relative density of soil particles is 2.691;
[0064] Among the samples pressed from the first soil sample, the second soil sample, and the mixture of the first soil sample and the second soil sample, all the samples have a relative density Dr=0.5, a confining pressure of 50 kPa, a shear rate of 0.1 mm / min, and a moisture content of 20%;
[0065] The sand mixing ratios of the mixture of the first soil sample and the second soil sample are 20%, 40%, 60% and 80% respectively.
[0066] Optionally, in step 2, the sample is continuously vacuumed for 4 hours, the sample preparation mold is placed in a freezer for 2 hours, and the natural thawing time is 8 hours.
[0067] Optionally, in step three, the triaxial shear test of the sample after natural dissolution using a CT-triaxial apparatus comprises the following steps:
[0068] Connect the water inlet valve of the pressure chamber to the water pump, turn on the water pump to inject distilled water into the cavity of the pressure chamber, open the exhaust port on the upper part of the pressure chamber to ensure that all the air in the cavity of the pressure chamber is exhausted to avoid bubbles affecting the test results;
[0069] Adjusting the volume pressure controller so that the sample base rises slowly until the sample top cap contacts the upper wall of the pressure chamber;
[0070] The parameters of the confining pressure and the shear rate are input into the control interface of the CT-triaxial instrument to start the test. The data acquisition box starts to collect the test data of the sample. The test data includes principal stress difference, axial strain, and volume deformation data. The test data is presented in the form of graphics.
[0071] Optionally, in step 1, the mass calculation process of each particle group in the mixture of the first soil sample and the second soil sample is as follows:
[0072] 1) According to the relative density Dr required for the test, the porosity ratio e of the first soil sample and the second soil sample is calculated using the following formula:
[0073]
[0074] In the formula, e max is the porosity ratio in the loosest state, called the maximum porosity ratio; e min is the minimum porosity, i.e. the porosity in the densest state; e is the natural porosity.
[0075] 2) According to the void ratio, the dry density of the first soil sample and the second soil sample under the condition of known relative density can be obtained, and the calculation formula is:
[0076]
[0077] Where Gs is the relative density of particles, ρ w is the density of water, ρ w =1g / cm 3 .
[0078] 3) During the calculation process, ensure that the volume V of the first soil sample c The second soil sample volume V q The sum of the volumes of the shear box remains unchanged;
[0079] 4) The mass m of the first soil sample can be calculated according to the set sand mixing rate Rs c and the mass of the second soil sample m q , the calculation formula of the sand mixing rate of the mixture is:
[0080]
[0081] Where, Rs is the sand mixing rate (%); m q is the mass of quartz sand in dry state (g), m c is the mass of coral sand in dry state (g); ρ dq is the dry density of quartz sand (g / cm3), ρ dc is the dry density of coral sand (g / cm3); V is the sample volume (cm3), which is equal to the shear box volume, V c is the volume of coral sand (cm3); when the sand mixing rate is 0%, V = V c , it is a pure coral sand sample; when the sand mixing rate is 100%, it is a pure quartz sand sample.
[0082] Embodiment 1
[0083] 1. Test materials and instruments
[0084] (1) This embodiment takes calcareous coral sand taken from an island reef in the South my country Sea and quartz sand taken from Fujian, my country as examples. Coral sand is off-white in color, contains impurities such as coral, giant clam, shell and coke, and has a fishy smell; quartz sand is milky white with red, or colorless and transparent. There are certain differences in the shape of the particles. The shape of coral sand is irregular, mainly in the form of flakes and grains, while the shape of quartz sand is relatively stable, mainly in the form of round particles. They are washed and dried for use. The maximum porosity of coral sand is 1.41 and the minimum is 0.77, and the relative density of soil particles is 2.739; the maximum and minimum porosity of quartz sand are 0.725 and 0.485 respectively, and the relative density of soil particles is 2.691.
[0085] In this embodiment, since the coral sand soil material is transported to the laboratory, the water content is low. In order to achieve the target water content of this test, the water content is adjusted by spraying. The coral sand particles are spread in an enamel dish, and the required water volume is obtained according to the calculation, and sprayed evenly on the sample surface through a spray bottle. After the sample surface is evenly wetted, the coral sand is mixed. Then the coral sand is leveled and evenly sprayed. This is repeated until the required water volume is sprayed in the sample. The obtained coral sand soil material is sealed and left to stand for more than 72 hours, and then the final water content is determined by drying method.
[0086] (2) In this embodiment, the ring shearing sample making equipment includes a sample pressing device and a sample making mold. The sample making mold includes four parts, namely a shear box, an inner ring, an outer ring and a height control steel ring. Since different relative density samples need to be configured, the volume of the soil in a loose state exceeds the volume of the shear box, so the inner ring, the outer ring and the height control steel ring are used to press the ring samples of different densities. The ring shearing sample making equipment belongs to the prior art and will not be described here. In this embodiment, the shear box volume used is 60cm 3 .
[0087] For the calcareous coral sand and its mixture in a dry state, the sample raw materials are dried in an oven, and the rain-fall method is used for loading without vibration. The calcareous coral sand and the mixture are dropped into the shear box at a distance of 5 cm from the shear box through a funnel, and a static compaction is performed using a mold.
[0088] (3) This embodiment uses a self-developed CT-triaxial instrument. The biggest feature of this instrument is its miniaturization. The triaxial pressure chamber can be placed vertically in the scanning hole of the CT machine. Through scanning, the structural evolution characteristics of the longitudinal section shear process can be observed. The instrument can also be placed flat on the CT machine scanning bed to observe the change law of the transverse section of the triaxial sample.
[0089] The instrument consists of a pressure chamber and a volume pressure controller. The top cover, base and side walls of the pressure chamber are made of acrylic glass. The loading system is made of peek material (polyetheretherketone). The loading system is Bishop loading mode, which removes the reaction frame in the previous triaxial instrument and reduces the metal artifacts of X-ray scanning imaging. Due to the limitation of the CT machine, the volume of the CT-triaxial pressure chamber must be reduced. This instrument uses a single double-sided pressure-resistant rolling diaphragm, which not only reduces the length of the piston rod and the overall height of the instrument, but also reduces the friction of axial loading. The height of the instrument is 45cm, and the maximum diameter of the outer shape is 20cm, which meets the minimum size requirements of the CT machine hole and is easier to complete the scanning of the longitudinal section of the sample in the CT. During the test, the instrument is placed vertically in the scanning hole of the CT machine. During the test, the position of the instrument is no longer adjusted, and the longitudinal large section (height 80mm, width 39.1mm) is directly scanned. On the one hand, the influence of moving the instrument and metal material artifacts on the test data acquisition is avoided; on the other hand, the changes in the shape of the sample during the triaxial shear process can be observed in real time. The maximum range of the instrument for axial pressure loading is 1MPa, and the maximum range of confining pressure loading is 400kPa. The volume pressure controller is produced by Xi'an Kangtuoli Company. The instrument can control the pressure by the amount of pure water pumped in, and its volume accuracy can reach 1mm 3 .
[0090] (4) The CT machine used in this embodiment is SOMATOMCscope produced by Shanghai Siemens Medical Devices Co., Ltd. The instrument has 24 rows of detectors and 16 detector slices; the maximum X-ray tube current is 345mA, the maximum X-ray voltage is 130kV, the number of uninterrupted scans in each range is 99, the slice thickness is 0.6-19.2mm, the maximum scanning time is 100s, the scanning length is 1530mm, and the conventional application pitch is 0.4-2.0.
[0091] 2. Experimental steps
[0092] 1. Sample preparation: The collected coral sand and quartz sand were used to prepare 6 groups of samples using a ring shear sample preparation device. All 6 groups of samples were saturated and had a relative density of Dr = 0.5, a confining pressure of 50 kPa, and a shear rate of 0.1 mm / min. Sample 1# was a coral sand sample, 2#-5# were coral sand-quartz sand mixture samples, and 6# was a quartz sand sample. The sand mixing rates Rs of samples 1-6# corresponded to 0%, 20%, 40%, 60%, 80%, and 100%, respectively, as shown in Table 1:
[0093] Table 1
[0094]
[0095]
[0096] 2. Vacuum and saturate the sample
[0097] Combined with the actual conditions of the laboratory, the sample is vacuumed and saturated. The pressed sample and the sample preparation mold are placed in a vacuum saturation cylinder filled with water. A permeable stone is placed on the upper and lower parts of the mold. The vacuum is continuously drawn for 4 hours, and then the mold is placed in a freezer for 2 hours. After the sample is prepared, it is demolded and loaded. Figure 3 As shown, in order to avoid the reduction or even failure of the effective confining pressure due to the poor airtightness of the latex membrane, two layers of sealing rubber rings are used to embed on the upper and lower sides of the latex membrane when loading the sample, and the connection between the latex membrane and the base and the top cap are fixed in two ways to keep the sample in a closed state. Then dissolve naturally for 8 hours.
[0098] 3. After the sample is saturated and installed, perform the triaxial shear test. First, connect the water inlet valve of the pressure chamber to the water pump, open the water pump to inject distilled water into the cavity of the pressure chamber, open the exhaust port on the top of the pressure chamber, and ensure that all the air in the cavity is discharged to avoid bubbles from affecting the test results. Then adjust the volume pressure controller of the axial pressure so that the base of the sample rises slowly until the top cap of the sample is in micro-contact with the upper wall of the pressure chamber. Finally, according to the parameters of the test plan, enter the confining pressure and shear rate in the control interface of the instrument software, and click Start to start the test. The instrument begins to collect basic data such as the principal stress difference, axial strain, volume deformation, etc. of the sample, and presents them in the form of graphics.
[0099] After the test is completed, the confining pressure is released, the water in the pressure chamber is manually drained and the pressure chamber is removed, the test samples are taken out and sieved to obtain the particle grading curve, and then the particle crushing law is studied.
[0100] It should be noted that the samples need to be screened before and after the test, using a special sieve with sieve hole diameters of 2mm, 1.43mm, 1.0mm, 0.85mm, 0.5mm, 0.3mm, 0.2mm, 0.1mm, 0.075mm, 0.0385 and 0.01mm. Based on the screening results, the particle gradation curve is obtained.
[0101] 3. Results Analysis
[0102] 1. Analysis of deformation and strength characteristics
[0103] Mixed sands with different sand mixing ratios show different strength characteristics and failure features under external loads. Figure 4 This is the relationship between the deviatoric stress and axial strain curves under different sand mixing rates (Rs=0%, Rs=20%, Rs=40%, Rs=60%, Rs=80%, Rs=100%) and confining pressure of 50 kPa.
[0104] Depend on Figure 4It can be seen that the deviator stress-axial strain curves of the coral sand samples under different sand mixing rates all have peak values, showing strain softening characteristics. If the particles of the sample are broken before reaching the ultimate sliding friction strength, the slip of the particles will cause the sample strength to decrease, indicating that the sample is damaged, making the stress-strain curve softening damage. With the increase of the sand mixing rate Rs, the peak strength and residual strength are reduced, and the axial strain corresponding to the peak value of the deviator stress gradually decreases, and the shear modulus increases. The reason for this phenomenon is that quartz sand and coral sand have different particle characteristics. When the initial conditions are the same, the overall structure of the coral sand is looser and easier to be compressed, while the addition of quartz sand increases the overall stiffness of the sample.
[0105] Coral sand and its mixtures are single-particle structures with point contact as the main feature. The particles are interlocked with each other. As the stress increases, the soil particles near the shear zone will adjust their positions (displacement, rolling, etc.), causing volume changes. Volume increase is called shear expansion, which is represented by a negative number; volume decrease is called shear contraction, which is represented by a positive number. Figure 5 It is the volume strain-axial strain relationship curve during the shear process with different sand mixing rates (Rs=0%, Rs=20%, Rs=40%, Rs=60%, Rs=80% and Rs=100%) under the confining pressure of 50kPa.
[0106] Depend on Figure 5 It can be seen that the volume strain-axial strain relationship curve of coral sand and its mixture has an obvious peak, showing a shear contraction-dilatation relationship. In the early stage of shear, the sample was compressed and the overall volume became smaller, and then with the increase of axial strain, the sample showed obvious dilatation phenomenon. At this time, the sample has been in a dilatation development trend. With the increase of sand mixing rate, the volume change trend also changes. With the increase of the mass of quartz sand, the overall dilatation trend of the mixture gradually increases. Analysis shows that the main reason why the sand mixing rate affects the volume change of the sample is particle crushing and shape. Because the particle shape of quartz sand is more regular and the degree of bite between particles is lower, it is easier for particles to adjust their position and form dilatation during the shear process. In addition, the particle strength of quartz sand is greater than that of coral sand. During the shear process, the particles are less broken, and the pores between particles cannot be filled, which is easier to form dilatation.
[0107] 2. Analysis of particle crushing rules
[0108] In this embodiment, the sample has particle crushing in both the consolidation and shearing processes, and the particle crushing measured this time is the sum of the particle crushing in the two stages. Figure 2 is the particle gradation curve before and after the test, Figure 2 It can be seen that the particle grading curve will gradually move to the lower left as the quartz sand mixing rate increases, indicating that with the increase of the sand mixing rate, the number of small particles and particle breakage in the sample after the test continue to decrease.
[0109] This is because during the shearing process, the particles mainly slide and roll. At the beginning of the test, the particles at both ends gradually move toward the middle, and the sample as a whole is axially compressed, and the contact between the particles becomes closer. Since the shape of quartz sand is irregular, without edges and corners, and has high strength, the edges and corners of the particles are not easy to break during this process. When the internal particles are squeezed, the particles cannot be displaced. Under the action of external force, the particles are sheared and damaged. Since the shape of quartz sand particles is relatively regular, it plays a certain lubricating role during the shearing process, which reduces the crushing. Therefore, as the mass of quartz sand increases, the base number of broken particles will decrease, and the sand mixing rate is negatively correlated with particle crushing.
[0110] 3. Characteristics of microstructure evolution
[0111] Depend on Figure 6 It can be seen that the overall uniformity of the coral sand sample in the initial state is poor, and there are individual holes inside, but no obvious cracks. As the shear progresses, until the axial strain reaches 3%, the particles slide relative to each other under the action of confining pressure and axial pressure, making the sample gradually dense, the holes are compressed, and the contact between the particles becomes closer, which is manifested as a decrease in volume on a macro scale. When the axial strain is 4%, microcracks begin to appear in the upper left part; at 5%, the particles of the sample are completely bitten, and as the axial strain continues to increase, the sample begins to bulge slightly, proving that the particles begin to move toward both ends under the action of external force, and the sample has reached peak strength when the axial strain is 4%-5%. When the axial strain is 10%, the lateral bulging of the sample further increases; when the axial strain reaches 15%, the sample is shaped like a drum as a whole. Due to the constraints at both ends of the sample, the particles can only rotate toward the middle of the sample, so the lateral movement displacement of the sample particles decreases from the middle to the two ends, which is manifested macroscopically as the middle of the sample gradually bulging, the overall volume increases, and it is shaped like a drum. Figure 7 It can be seen that the failure form of the sample with a sand mixing ratio of 20% is similar to that of coral sand, and no shear band is produced. However, unlike coral sand, the axial strain when it starts to bulge outward is smaller than that of coral sand (3%).
[0112] Depend on Figure 8 It can be seen that when the axial strain of the sample with a sand mixing ratio of 40% reaches 3%, microcracks appear in the lower left part of the sample and the shear band starts to start, proving that the sample has been completely compressed at this time. As the shearing progresses, the particles rotate and the cracks gradually extend, proving that the sample has reached peak strength when the axial strain is 3%-4%. When the axial strain reaches 4%, microcracks gradually appear in the lower right part of the sample. When the axial strain is 7%, the shear band runs through. When the axial strain is 10%, the lateral bulging of the sample increases further. When the axial strain reaches 15%, the bulging degree of the middle right side of the sample is large, and the shear band can be clearly observed. Fig. 9 , Fig.10 , Fig.11 It can be seen that the axial strains of the Rs=60%, 80% and quartz sand samples when they are completely compressed and begin to have microcracks are 3%, 2% and 1% respectively; the axial strains corresponding to the volume expansion of samples with different sand doping ratios are 3%, 2-3% and 2% respectively, proving that the Rs=60%, 80% and quartz sand samples have reached peak strength at axial strains of 3%, 2-3% and 2% respectively, and the higher the sand doping ratio, the greater the sliding displacement of the sample on the shear plane, which is manifested as a greater volume expansion on a macroscopic scale, which is consistent with the stress-strain curve obtained from the test. Since the formation location of the shear band is random, the direction of the shear band of the Rs=80% sample is perpendicular to the scanning surface, so the direction of the longitudinal section shear band obtained by scanning is inconsistent with that of the other samples. After the shearing is completed, the instrument is rotated 90° to additionally shoot the shear band after shearing ( Fig.12 The shear band after shearing is completed and the actual picture), its development trend is consistent with the other samples. In summary, with the increase of sand mixing rate, the time for the sample to be compressed, the shear band to start and be fully formed becomes shorter (the sample with sand mixing rate less than 40% will not even have a shear band), and the volume expansion is greater.
[0113] The reason for this phenomenon is related to the different physical and mechanical properties of coral sand and quartz sand. The shape of coral sand particles is irregular, with many edges and corners, and it is easy to break. On the contrary, quartz sand is mostly round or quasi-round, with smoother surface and higher Mohs hardness (about 7), which is not easy to break. During the compression process, coral sand particles slide under the action of external force, making the contact between particles closer. When the particles are fully bitten, the continuous shearing breaks the edges and corners of the particles into smaller particles, filling the pores, making the sample further compressed and denser; when the quartz sand particles are fully in contact, the sliding of the particles is restricted, and because the particles are not easy to break, the sample cannot be further compressed, so the compression time of the sample becomes shorter. After the sample is completely compressed, the particles begin to roll, and the peak strength is reached at this time. Therefore, the axial strain corresponding to the peak strength of the sample with a higher sand mixing rate is smaller. The formation of shear bands is mainly due to the mutual rotation between particles. Since the sliding friction and biting friction between quartz particles are smaller than those of coral sand, the rotation between particles of the sample with a smaller sand mixing rate is smaller, so the sample with a small sand mixing rate will not have shear bands. After the shear band of the sample with a large sand-doping ratio is formed, under the same axial strain, the sample with a higher sand-doping ratio slides along the shear band for a longer distance, which is manifested macroscopically as a greater volume expansion.
[0114] 4. The connection between micro data and macro phenomena
[0115] In this embodiment, the absorption coefficient μ of each material point on the longitudinal section obtained by the CT machine is converted into a CT number by the following formula:
[0116]
[0117] In the formula: CT number refers to the strength of X-ray absorption at a certain point, μthe substance refers to the absorption coefficient of a certain substance to X-rays, Refers to the absorption coefficient of pure water to X-rays.
[0118] According to the CT number of all material points in the selected area on a certain section, the CT machine can calculate the total CT value, ME value and SD value of the area according to relevant specifications. The ME value can be used to obtain the variation law of the average density of the selected area. The SD value is the variance value at a certain confidence level, which reflects the unevenness of the sample density in the selected area and indirectly reflects the strength of the sample structure.
[0119] In order to quantitatively analyze the structural evolution of the specimen, all areas within the boundary of the longitudinal section of the specimen were selected to measure the CT values, such as Fig.13 Due to space limitations, this paper only lists the schematic diagram of the measurement of sample 1#, and the ME values and SD values of the remaining samples are shown in Table 2.
[0120] Table 2
[0121]
[0122] In order to more intuitively show the variation of the CT value of the specimen with vertical strain, Fig.14 , Fig.15 The curves of ME value and SD value changing with axial strain. As can be seen from the figure, with the increase of axial strain, the ME value of the sample will rise slightly and then fall; the SD value will first fall and then rise. Taking the coral sand sample as an example, when the axial strain of the coral sand sample is less than 3%, the ME value is positively correlated with the axial strain, and the SD value is negatively correlated with the axial strain, indicating that in the early stage of shear, the sample begins to be compressed under the action of deviatoric stress, making it denser and the particle arrangement more dense and uniform, and the porosity decreases. When the axial strain is 3%, the ME value of the coral sand sample reaches the maximum and the SD value reaches the minimum. At this time, the sample is in the densest and most uniform state, which is manifested as a decrease in volume, that is, shear shrinkage, on a macro scale. After reaching the peak point, as the shear progresses, the ME value decreases with the increase of axial strain, and the SD value increases with the increase of axial strain. This shows that cracks begin to appear inside the sample and gradually expand into shear bands. The particles begin to move to both ends under the action of external force. At this time, the sample begins to bulge slightly, and the uniformity and density inside the sample decrease, resulting in a decrease in ME value and an increase in SD value. Macroscopically, it manifests as an increase in volume, that is, shear expansion.
[0123] Comparing the samples with different sand mixing ratios, the axial strain corresponding to the peak points of ME and SD values will decrease with the increase of sand mixing ratio (3% for coral sand and only 1% for quartz sand). It can be considered that the increase of sand mixing ratio will shorten the time for the sample to be compressed and the time for the shear band to start.
[0124] In order to explore the crushing characteristics and mesoscopic structural evolution of coral sand and coral sand-quartz sand mixture, a mesoscopic real-time dynamic scanning of triaxial shear and compression process was carried out. The test results show that:
[0125] (1) With the increase of sand mixing ratio Rs, both the peak strength and residual strength decrease, and the axial strain corresponding to the peak value of the deviatoric stress gradually decreases. The volume deformation of coral sand and its mixture is affected by the sand mixing ratio. As the mass of quartz sand increases, the overall dilatancy trend of the mixture gradually increases.
[0126] (2) The sand-doping ratio has a great influence on the shear band and volume change of the sample. When the sand-doping ratio is less than 40%, no shear band will appear. When the sand-doping ratio is greater than 40%, as the sand-doping ratio increases, the time for the sample to be compressed, the time for the shear band to start and be fully formed becomes shorter, and the volume expansion becomes greater.
[0127] (3) During the triaxial shear process, as the axial strain increases, the ME value of each sample increases first and then decreases, and the SD value decreases first and then increases. This indicates that the sample was compressed and became dense and uniform in the early stage. In the later stage, due to the appearance of the shear band, the density of the sample decreased and the uniformity deteriorated. The horizontal coordinate corresponding to the inflection point of the ME value, SD value-axial strain curve is the axial strain corresponding to the initiation of the shear band. The changes in the ME value and SD value can detect the generation of microcracks inside the sample earlier.
[0128] The above is only the best specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions within the technical scope disclosed in the present application shall be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for testing the dilatancy and shear band evolution of sand, characterized in that: The following steps are involved: Step 1, preparing samples: collecting first soil samples and second soil samples from different target sites, washing and drying them respectively, performing screening tests on the first soil samples and the second soil samples to obtain particle grading curves of the first soil samples and the second soil samples, and then pressing the first soil samples, the second soil samples, and a mixture of the first soil samples and the second soil samples after drying respectively through a sample preparation instrument to obtain multiple samples; Wherein, the first soil sample is coral sand, and the second soil sample is quartz sand; Step 2: Vacuum and saturate the sample: put all the pressed samples together with the sample preparation mold of the sample preparation instrument into a vacuum saturation cylinder filled with water, place a permeable stone on the upper and lower parts of the sample preparation mold, vacuumize continuously, then put the sample preparation mold into a freezer for freezing, demould and sample loading, and dissolve naturally; Step 3: using a CT-triaxial instrument to perform a triaxial shear test on the sample after natural dissolution, performing a microscopic real-time dynamic scan of the triaxial shear and compression process of the sample, and collecting test data; The CT-triaxial instrument includes a pressure chamber, a volume pressure controller and a data acquisition box. During the test, the pressure chamber is placed vertically in the scanning hole of the CT machine. The volume pressure controller controls the pressure by the amount of pure water pumped in. The data acquisition box is used to collect the test data. Step 4: After the test is completed, the sample after the test is taken out and sieved, and the particle crushing law of the sample is obtained according to the particle grading curve of the sample before and after the test; by performing deformation and strength characteristic analysis and structural evolution analysis on the test data, the purpose of testing the shear dilatancy and shear band evolution of the sample is achieved.
2. The method for testing the dilatancy of sand and the evolution of shear bands according to claim 1, characterized in that: In step 1, the sample preparation instrument adopts a standard triaxial sample preparation device, and the sample preparation device includes a sample pressing device and a sample preparation mold; The sieving test was carried out using special sieves with sieve hole diameters of 2 mm, 1.43 mm, 1.0 mm, 0.85 mm, 0.5 mm, 0.3 mm, 0.2 mm, 0.1 mm, 0.075 mm, 0.0385 and 0.01 mm, respectively.
3. The method for testing the dilatancy of sand and the evolution of shear bands according to claim 1 or 2, characterized in that: In step 1, the first soil sample is coral sand, with a maximum porosity ratio of 1.41, a minimum porosity of 0.77, and a relative density of soil particles of 2.739; The second soil sample is quartz sand, the maximum and minimum porosity ratios of the quartz sand are 0.725 and 0.485 respectively, and the relative density of soil particles is 2.691; Among the samples pressed from the first soil sample, the second soil sample, and the mixture of the first soil sample and the second soil sample, all the samples have a relative density Dr=0.5, a confining pressure of 50 kPa, a shear rate of 0.1 mm / min, and a moisture content of 20%; The sand mixing ratios of the mixture of the first soil sample and the second soil sample are 20%, 40%, 60% and 80% respectively.
4. The method for testing the dilatancy of sand and the evolution of shear bands according to claim 3, characterized in that: In step 2, the sample is continuously vacuumed for 4 hours, the sample preparation mold is placed in a freezer for 2 hours, and the natural dissolution time is 8 hours.
5. The method for testing the dilatancy of sand and the evolution of shear bands according to claim 4, characterized in that: In step 3, the triaxial shear test is performed on the sample after natural dissolution using a CT-triaxial apparatus, comprising the following steps: Connect the water inlet valve of the pressure chamber to the water pump, turn on the water pump to inject distilled water into the cavity of the pressure chamber, open the exhaust port on the upper part of the pressure chamber to ensure that all the air in the cavity of the pressure chamber is exhausted to avoid bubbles affecting the test results; Adjusting the volume pressure controller so that the sample base rises slowly until the sample top cap contacts the upper wall of the pressure chamber; The parameters of the confining pressure and the shear rate are input into the control interface of the CT-triaxial instrument to start the test. The data acquisition box starts to collect the test data of the sample. The test data includes principal stress difference, axial strain, and volume deformation data. The test data is presented in the form of graphics.
6. The method for testing the dilatancy and shear band evolution of sand according to claim 3, characterized in that: In step 1, the mass calculation process of each particle group in the mixture of the first soil sample and the second soil sample is as follows: 1) According to the relative density Dr required for the test, the porosity ratio e of the first soil sample and the second soil sample is calculated using the following formula: In the formula, e max is the porosity ratio in the loosest state, called the maximum porosity ratio; e min is the minimum porosity, i.e. the porosity in the most dense state; e is the natural porosity; 2) According to the void ratio, the dry density of the first soil sample and the second soil sample under the condition of known relative density can be obtained, and the calculation formula is: Where Gs is the relative density of particles, ρ w is the density of water, ρ w =1g / cm 3 ; 3) During the calculation process, ensure that the volume V of the first soil sample c The second soil sample volume V q The sum of the volumes of the shear box remains unchanged; 4) The mass m of the first soil sample can be calculated according to the set sand mixing rate Rs c and the mass of the second soil sample m q , the calculation formula of the sand mixing rate of the mixture is: Where, Rs is the sand mixing rate (%); m q is the mass of quartz sand in dry state (g), m c is the mass of coral sand in dry state (g); ρ dq is the dry density of quartz sand (g / cm 3 ), ρ dc is the dry density of coral sand (g / cm 3 ); V is the sample volume (cm 3 ), whose value is equal to the shear box volume, V c is the volume of coral sand (cm 3 ); When the sand mixing rate is 0%, V = V c , it is a pure coral sand sample; when the sand mixing rate is 100%, it is a pure quartz sand sample.